System and method for sharing data between large data volume and organizations - ZHANG HE; LAN YONG; ZHANG SIBO; GAO ZHIKANG (2023)
The invention discloses a data sharing system used between a large data volume and an organization. The data sharing system comprises an algorithm library, a service end, an encryption algorithm server end, a cloud storage encryption storage service and a block chain, the algorithm library comprises a data signature library, a proxy re-encryption library and a group signature library, and provides algorithm functions for the service end and the encryption algorithm server end. The method has the beneficial effects that the block chain technology, the digital envelope technology and the cloud storage technology are comprehensively used, safe and efficient storage in the case of large data volume is realized, the network transmission requirement is reduced, and the requirements of non-tampering, non-repudiation, traceability and the like of the data are ensured; and the data privacy security is effectively protected. 本发明公开了一种用于大数据量与组织间的数据共享系统，包括算法库、业务端、加密算法服务端、云存储加密存储服务、区块链；所述算法库包括：数据签名库、代理重加密库、群签名库，为业务端和加密算法服务